2021
DOI: 10.1002/adtp.202100036
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutase‐Loaded Nanoparticles Attenuate Myocardial Ischemia‐Reperfusion Injury and Protect against Chronic Adverse Ventricular Remodeling

Abstract: Early revascularization is critical to reduce morbidity after myocardial infarction, although reperfusion incites additional oxidative injury. Superoxide dismutase (SOD) is an antioxidant that scavenges reactive oxygen species (ROS) but has low endogenous expression and rapid myocardial washout when administered exogenously. This study utilizes a novel nanoparticle carrier to improve exogeneous SOD retention while preserving enzyme function. Its role is assessed in preserving cardiac function after myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…The mitochondrial iron reserve was thus considered a major factor in determining cardiomyocyte fate ( Wofford et al, 2017 ). Therefore, the protection of mitochondria against damage plays an important role in alleviating myocardial I/R injury, which may be an attractive strategy to suppress I/R injury ( Wu et al, 2019 ; Altshuler et al, 2021 ). In this research, HJ11 decoction treatment attenuated mitochondrial damage and increased ATP and mtDNA levels in the myocardial I/R injury rat model and cell model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitochondrial iron reserve was thus considered a major factor in determining cardiomyocyte fate ( Wofford et al, 2017 ). Therefore, the protection of mitochondria against damage plays an important role in alleviating myocardial I/R injury, which may be an attractive strategy to suppress I/R injury ( Wu et al, 2019 ; Altshuler et al, 2021 ). In this research, HJ11 decoction treatment attenuated mitochondrial damage and increased ATP and mtDNA levels in the myocardial I/R injury rat model and cell model.…”
Section: Discussionmentioning
confidence: 99%
“…Acute myocardial infarction (AMI) is one of the leading causes of disability and death globally and imposes severe burden on health and economy ( Altshuler et al, 2021 ). More than seven million patients suffer from AMI every year, and untreated AMI cases contribute to approximately 30% of all AMI-related deaths ( Beom et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an effective ROS scavenger can alleviate a myocardial injury to some extent. It has been reported that SOD [ 18 ] and GPX [ 19 ] have a significant therapeutic effect on the myocardial injury. PRDX6, as an important antioxidant protein, can scavenge many kinds of peroxides, such as hydrogen peroxide, fatty hydroperoxides, short-chain hydroperoxides, and phospholipid hydroperoxides to protect the body from oxidative stress damage based on its GPX activity [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 110 ] Intramyocardial injection of ROS‐responsive nanoparticles into animal models lead to improved cardiac function and reduction in the infarct size. Furthermore, plasma exosomes, [ 111 ] superoxide dismutase‐loaded porous nanoparticles, [ 112 ] and ROS‐responsive hydrogel, carrying fibroblast growth factor [ 113 ] were developed. These nanoplatform‐based ROS scavengers can remove ROS to the greatest extent and can satisfactorily treat myocardial IRI.…”
Section: Nanoplatform‐based Ros Scavengers For the Therapy Of Irimentioning
confidence: 99%